Upregulation of Voltage-Gated Calcium Channel Cav1.3 in Bovine Somatotropes Treated with Ghrelin. (18th December 2013) - Salinas Zarate, V. M.; Magdaleno Méndez, A.; Domínguez Mancera, B.; Rodríguez Andrade, A.; Barrientos Morales, M.; Cervantes Acosta, P.; Hernández Beltrán, A.; Romero Salas, D.; Flores Hernández, J. L. V.; Monjaraz Guzmán, E.; Félix Grijalva, D. R.
Abstract : Activation of the growth hormone (GH) secretagogue receptor (GHS-R) by synthetic GH releasing peptides (GHRP) or its endogenous ligand (Ghrelin) stimulates GH release. Though much is known about the signal transduction underlying short-term regulation, there is far less information on the mechanisms that produce long-term effects. In the current report, using an enzyme-linked immunosorbent assay for GH detection and whole-cell patch-clamp recordings, we assessed the long-term actions of such regulatory factors on voltage-activated Ca 2+ currents in bovine somatotropes (BS) separated on a Percoll gradient and detected by immunohistochemistry. After 24 h of treatment with Ghrelin (10 nM) or GHRP-6 (100 nM) enhanced BS secretory activity; GH secretion stimulated by GHS through the activation of GHS-R because treatment with the antagonist of GHS-R (D-Lys3-GHRP-6, 10 μ M) blocked the GH secretion, and the effect was dose and time dependent (24, 48, and 72 h). GH secretion stimulated by GHRP-6 was abolished by nifedipine (0.5 μ M), a blocker of L-type HVA Ca 2+ channels, and KN-62 (10 μ M), an inhibitor of Ca 2+ /CaM-KII. After 72 h in culture, all recorded BS exhibited two main Ca 2+ currents: a low voltage-activated (LVA; T-type) and a high voltage-activated (HVA; mostly dihydropyridine-sensitive L-type) current. Interestingly, HVA and LVA channels were differentially upregulated by Ghrelin. Chronic treatment with the GHS induced a significant selective increase on the Ba 2+ current through HVA Ca 2+ channels, and caused only a small increase of currents through LVA channels. The stimulatory effect on HVA current density was accompanied by an augment in maximal conductance with no apparent changes in the kinetics and the voltage dependence of the Ca 2+ currents, suggesting an increase in the number of functional channels in the cell membrane. Lastly, in consistency with the functional data, quantitative real-time RT-PCR revealed transcripts encoding for the Cav 1.2 and Cav 1.3 pore-forming subunits of L-type channels. The treatment with Ghrelin significantly increased the Cav 1.3 subunit expression, suggeting that the chronic stimulation of the GHS receptor with Ghrelin or GHRP-6 increases the number of voltage-gated Ca 2+ channels at the cell surface of BS.